Weight Measurement and Identification of Cow Type Using Computer Vision Method - Nugraha, Ucu; Purno Wahyu, Ari (International Journal of Engineering and Technology, 2018)
Cows are farm animals that have been commonly cultivated in Indonesia and have become one of the cultures and can be used for meat and milk for consumption or cows can be used to plow rice fields, especially in areas where processing of agricultural land is still traditional, given the benefits of cattle farming. Very important in the current modern era, maintenance and feed factors are very influential on the quality of the condition of the cow that will affect the weight and size of the cow. The meat and feed processing system can now use computer technology or known as biotechnology and Smart Farmer namely the system, which can be used to monitor and identify the type of cow and even the state of the cow pen itself. Maintenance and monitoring techniques for the type and weight of cattle can use image processing techniques, where cow health and weight can be calculated by measuring the length and width of the chest circumference, the image processing system will accurately process and calculate the weight of cattle in 2D or 3D data display, segmentation process will be processed, while the introduction of the type of cow serves to determine the type, nature, and feed of the cow. This type of cattle measurement system with image processing can help farmers in this modern era to measure weight, recognize species, so as to save time and effort without hurting habitat and disrupting cattle growth.Â